A Method for Reviewing the Accuracy and Reliability of a Five-Level Triage Process (Canadian Triage and Acuity Scale) in a Community Emergency Department Setting: Building the Crowding Measurement Infrastructure. (11th January 2012) - Howlett Howlett, Michael K. Michael K.; Atkinson Atkinson, Paul R. T. Paul R. T.
Abstract : Objectives. Triage data are widely used to evaluate patient flow, disease severity, and emergency department (ED) workload, factors used in ED crowding evaluation and management. We defined an indicator-based methodology that can be easily used to review the accuracy of Canadian Triage and Acuity Scale (CTAS) performance. Methods. A trained nurse reviewer (NR) retrospectively triaged two separate month's ED charts relative to a set of clinical indicators based on CTAS Chief Complaints. Interobserver reliability and accuracy were compared using Kappa and comparative statistics. Results. There were 2838 patients in Trial 1 and 3091 in Trial 2. The rate of inconsistent triage was 14% and 16% (Kappa 0.596 and 0.604). Clinical Indicators "pain scale, chest pain, musculoskeletal injury, respiratory illness, and headache" captured 68% and 62% of visits. Conclusions. We have demonstrated a system to measure the levels of process accuracy and reliability for triage over time. We identified five key clinical indicators which captured over 60% of visits. A simple method for quality review uses a small set of indicators, capturing a majority of cases. Performance consistency and data collection using indicators may be important areas to direct training efforts.